INFORMATION SYSTEM OF TESTING LABORATORY FOR RADIATION CONTROL - K. Yu. Kolybanov; R. E. Kuzin; S. S. Pisanenko; T. N. Tairov (Тонкие химические технологии)
Development of information-analytical system of radiation control is based on existing methods and hardware-software measuring instruments for the purpose of systematizing, storing and processing the results of analysis of samples of various composition and origin. Studying a large flow of environmental and technological samples includes the most difficult task to ensure the required accuracy of calculation of activities and errors, especially at low activities levels at the threshold of detectable area. The information system hardware includes a set of devices designed to measure the activity of the samples, and a local computer network. The server part of the software package includes a client-server database management system and a web application for database administration. In addition to the standard programs included in the delivery of radiometric equipment the client part of the software package includes the program "ODRA", developed using object-oriented language C# in Microsoft Visual Studio. The program "ODRA" includes modules for calculating the specific (volumetric) activity of radionuclides in low-active samples of materials and environmental objects, as well as for calculating the relative and absolute error of activity determination. The program has a convenient graphical user interface for database communication. The information system of the radiation testing laboratory of the enterprise that conducts work with radioactive materials has undergone a four-year approbation in the experimental production mode at VNIIHT in 2014-2017 and can significantly reduce the processing time of the results of determining the radioactivity of technological and environmental samples and reduce the operator error factor.